Mind in the waters a book to celebrate the consciousness of whales and dolphins - McIntyre, Joan (Charles Scribner's Son, 1974)
Calls attention to the need to stop the senseless murder of whales and dolphins and promotes a human awareness of the sensitivity and creativity of these creatures.